EKSISTENSI DAN PERAN ALAT BUKTI ELEKTRONIK DALAM SISTEM PERADILAN DI INDONESIA: ALAT BUKTI ELEKTRONIK - lahati, teddy (Ikatan Hakim Indonesia (IKAHI), 2024)
Electronic evidence in the judicial legal system in Indonesia is something new so it has become an object of study in exploring its existence and role. The legality of electronic evidence has become a polemic about how the examination of electronic evidence is regulated in statutory regulations, what is the validity of electronic evidence, what is the procedure for authenticating electronic evidence in trial examinations, and what is the practice of examining electronic evidence in trials so that appropriate solutions must be found? to answer the legal phenomenon in question. This research is descriptive-analytic normative research, namely by examining existing regulations. Data collection is carried out by collecting regulations in the ITE Law, KUHAP, Perma, and the like. The results of the research conclude that First, electronic documents have received recognition as valid evidence in civil trials, in accordance with the Company Documents Law and ITE Law Number 11 of 2008, but as part of the procedural law, electronic documents do not yet have regulations on the procedures for submitting them in trial, procedures for showing it to the opposing party. Second, the technical submission and technical aspects of showing electronic documents at trial can be answered through clear regulations or technical instructions for Elitigation in practice at trial, but to provide legal certainty it needs to be regulated in the Civil Procedure Law or compiled in Supreme Court Regulations